Pearl Harbor - Wallace, Randall, 1949- (New York : Hyperion, 2001)
The story of Rafe and Danny, boyhood friends who are now both pilots, and the woman they both love.
Keywords: Pearl Harbor (Hawaii), Attack on, 1941 -- Fiction; World War, 1939-1945 -- Hawaii -- Pearl Harbor -- Fiction; Triangles (Interpersonal relations) -- Fiction; Air pilots, Military -- Fiction; Male friendship -- Fiction; Nurses -- Fiction; Pearl Harbor (Hawaii) -- Fiction; Fiction; Love stories; Movie novels; War stories